Analysis of Teachers’ Challenge in Online English Learning Assessment - Ummubisma Palra; Saepudin Saepudin; Zulfah Zulfah; Abd. Haris Sunubi; Arqam Arqam (Budapest International Research and Critics University, 2022)
This study aims to describe the kinds of online English learning assessment and the challenges of English teachers in online learning assessment. This research applied a qualitative descriptive as the research design. In collecting the data, the researcher applied interviews and documentation. They are knowledge assessment, skill assessment, and student’s attitude assessment. The online assessment and offline assessment was similar. The difference was the interaction, place, media and the way to take and give the students’ task because all the process through online. In online learning assessment the most challenging was students’ attitude assessment because the teacher difficult to control the students’ honesty, responsibility, students’ creativity, and students’ collaboration. The result of this research also showed the English teacher face some challange in online English learning assessment such as students’ behavior, Students’ less understanding of material, Facilities problems and scoring system.